BIOECOLOGY AND MEDICINAL PROPERTIES (SENNA ANGUSTIFOLIA DEL) - RAVSHANOVA UMIDA BAKHRIDDINOVNA (International Journal of Innovations in Engineering Research and Technology, 2021)
The morphological features of senna angustifolia - an holly herbaceous plant, flowering dynamics, the relationship with environmental factors were studied in the city of Termez, Surkhandarya region. Under conditions of introduction, senna angustifolia is recommended for cultivation under conditions of introduction, taking into account the ability to multiply by seeds, resistance to high and low temperatures, resistance to diseases and pests, and medicinal properties.